2021
DOI: 10.14202/vetworld.2021.2634-2639
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and molecular characterization of Leucocytozoon caulleryi from backyard chickens in Khon Kaen Province, Thailand

Abstract: Aim: The aim of this study was to characterize Leucocytozoon caulleryi from backyard chickens in Khon Kaen Province, Thailand. Materials and Methods: Tissue samples were collected from backyard chickens suspected to have leucocytozoonosis and subjected to histopathology examination. The BLAST Tool at NCBI GenBank (Basic Local Alignment Research Tools) (http://www.ncbi.nlm.nih.gov/BLAST) was used to identify the nucleotide sequence of the partial cytochrome c oxidase subunit I (cox I) gene. A Phylogenetic tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Reports in other galliform birds are absent. The parasite is virulent in domestic chickens, and the infection is often lethal in non-adapted chicken breeds [ 1 , 72 , 327 , 330 , 331 , 332 ]. Experimental studies have shown that a high degree of immunity develops in domestic chickens that survive acute infections.…”
Section: Resultsmentioning
confidence: 99%
“…Reports in other galliform birds are absent. The parasite is virulent in domestic chickens, and the infection is often lethal in non-adapted chicken breeds [ 1 , 72 , 327 , 330 , 331 , 332 ]. Experimental studies have shown that a high degree of immunity develops in domestic chickens that survive acute infections.…”
Section: Resultsmentioning
confidence: 99%
“…Haemosporidian infections in domestic hens and wild birds have been expanding in Thailand [ 39 , 40 , 41 , 42 ]. In the study by Pramual et al, [ 21 ] it was demonstrated that C. mahasarakhamense , C. guttifer , and C. huffi were infected with Leucocytozoon and two of P .…”
Section: Discussionmentioning
confidence: 99%
“…The L. caulleryi parasite is transmitted through the black fly ( Simuliidae ) and the biting midge ( Culicoides ) ( 21 , 41 ), which are widespread in Maha Sarakham ( 31 ). Recently, a study reported L. caulleryi -infected backyard chickens in Khon Kaen province ( 28 ), where the proximity to and border with Maha Sarakham indicated this parasite is endemic in this region. Such mixed amplification unforeseen in the protocol has previously occurred in samples from chickens from Myanmar, also because of the sequence similarity of the cytochrome b region between Plasmodium and Leucocytozoon ( 48 ).…”
Section: Discussionmentioning
confidence: 99%